Pengaruh Vermikompos dan Pupuk Kandang Terhadap Ketersediaan Hara dan Hasil Jagung Manis di Alfisol - Jauhari Syamsiyah; Hery Widijanto; Ganjar Herdiansyah; Arrajula Fatah laudzai (Agrosains : Jurnal Penelitian Agronomi, 2025)
Vermicompost is the product of organic matter decomposition by earthworms and has great potential as an environmentally friendly fertilizer. It contains natural growth hormones, enzymes, and active microorganisms, and is free from harmful pathogens and heavy metals, making it safe for both soil and plants. Alfisol soils, which are typically low in organic matter and essential macronutrients such as nitrogen (N), phosphorus (P), and potassium (K), require organic inputs to improve their fertility. This study aimed to evaluate the effects of vermicompost and manure on nutrient availability and sweet corn yield in Alfisols. The experiment was conducted using a completely randomized block design with treatments combining various doses of vermicompost and manure. Observed parameters included soil chemical properties, plant growth, and yield components. The results showed that the application of vermicompost at a dose of 1 ton/ha was not significantly different from 2 tons/ha of manure, but both treatments differed significantly from the control. The combined treatment of NPK and vermicompost (1 NPK + 2 vermicompost) increased nutrient availability and uptake, as well as sweet corn yield (total N: 0.68%, available P: 7.76 ppm, available K: 1.78 me/100 g, cob weight: 240.5 g). These findings confirm that vermicompost, as an organic nutrient source, is effective in supporting sustainable agricultural practices in marginal soils such as Alfisols, while reducing dependence on inorganic fertilizers.